ANALISIS PENILAIAN PERUSAHAAN HOTEL X BERDASARKAN METODE DISCOUNTED CASH FLOW - , Rory Rivanov, Boyke R. Purnomo, SE., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hotel X with average occupancy rate of 79% by 2011 is one of the three-star hotel managed without the services of a hotel operator has reasonably good performance in Jakarta on increased competition in the budget hotel segment that is generally controlled by the foreign hotel operators network such as Accor and local hotel chains such as Santika and Aston. The purpose of this study was to find the intrinsic value of Hotel X by using the Discounted Cash Flow method using data from the company's processed internal financial statements, the analysis of tourism factors in Indonesia and Indonesia's macroeconomic conditions in general so as to provide the adequate projection for use as a basis for calculating the fair value of the company. Assessment results by using the DCF method gives the value of the company of Rp. 216,963,161,753 or Rp. 216.963 per share before the effect of discounts due to illiquidity in the closed company at Rp. 190,385,174,438 after the effect of illiquidity discount for each stock group.